Pengaruh Pengolahan terhadap Kandungan Poliphenol dan Antosianin Beras Wulung yang Berpotensi sebagai Makanan Diet Penderita Diabetes Mellitus - Sri Hartati (Universitas Muhammadiyah Semarang, 2013)
Wulung rice called black rice in Java, it was believed the functional food for Diabetes Mellitus. The purpose studies was to determine the chemical content of rice like the moisture content, carbohydrate, protein, fat, ash and to know the changes in polyphenolic and anthocyanin levels after cooking and a flour product. The Results showed that is a carbohydrate (64.98% wb), protein 15.41% wb, fat 4.23% wb, minerals (ash) 2.04% wb, crude fiber 3.52% wb and moisture 13.34%. There were no differences between the levels of phenols for whole grain that has been processed into rice, but there were significant differences with flour. Total phenol of whole grain, flour, and rice respectively are 0.76, 0.55 and 0.84 mg. There were significant decreasing of anthocyanin in processing to the flour and rice. The decrease in anthocyanin 83.60% occur in the processing of rice. Anthocyanin of whole grain, flour and rice respectively: 2.8918, 2.4091 and 0.4741 mg/100g (% db).